Hybrid spin coating and evaporation techniques for fabricating double-layer stacked dual-color perovskite LEDs - Ching-Ho Tien; Jen-Yu Fang; Lung-Chien Chen (Scientific Reports)
Abstract This work reports on the preparation process of a double-layer perovskite active layer. The first active layer film, Cs2.9K0.2PEA0.4Pb2I3.9Br3.6, was fabricated using a spin-coating method, while the second active layer, MAPbBr3, was deposited using MAPbBr3 single crystals as the evaporation source. Additionally, doping the PEDOT: PSS hole transport layer with ETA and EDA can enhance the uniformity of the perovskite film and reduce voids, improving charge transport efficiency. It proposed the use of an MABr layer to passivate the device interface structure, enhancing the injection and recombination efficiency of charge carriers. In the study of the single-layer Cs2.9K0.2PEA0.4Pb2I3.9Br3.6 perovskite, the optimized brightness reached 513.4 cd/m², with an external quantum efficiency (EQE) of 0.24% after doping and modification. When the second active layer MAPbBr3 was introduced, the results showed that as the voltage increased from 4 V to 10 V, the LED emission color changed from orange-red to green. This change was attributed to the variation in the recombination positions of charge carriers in different bandgap materials at different voltages. At low voltage, carriers recombine in the layer with a smaller bandgap, emitting red light; whereas at high voltage, carriers recombine in the layer with a larger bandgap, emitting green light.